Risk of dementia or cognitive impairment in COPD patients: A meta-analysis of cohort studies - Wang, Jun; Li, Xuanlin; Lei, Siyuan; Zhang, Dong; Zhang, Shujuan; Zhang, Hailong; Li, Jiansheng (Frontiers in Aging Neuroscience, 2022)
Purpose: A meta-analysis of cohort studies was performed to evaluate the associa-tion between COPD and the risk of dementia or cognitive impairment. Methods: Cohort studies that evaluated the association between COPD and the risk of dementia or cognitive impairment were identified by a systematic search of PubMed, Embase, Web of Science, and Cochrane Library databases. The search time frame was from database establishment to April 12, 2022, with two reviewers independently screen-ing the literature and extracting data. The Newcastle-Ottawa Quality Assessment Scale (NOS) was used to conduct the quality evaluation. Then, a meta-analysis was performed using Stata 15.1 software. Results: Six cohort studies including 428,030 participants were included. The overall quality of the included studies was high, with an average NOS score of over 7. Meta-analysis showed that compared to those with-out COPD at baseline, patients with COPD were associated with a significant in-creased risk of dementia (RR = 1.24, 95% CI = 1.03 1.50, I2 = 96.6%, z = 2.25, p = 0.024) and cognitive impairment (RR = 1.30, 95% CI = 1.13 1.49, I2 = 50.1%, z = 3.72, p < 0.001). Subgroup analysis suggested no significant difference in the risk of dementia among COPD patients of different genders. Nevertheless, in terms of age, the risk of dementia varied among COPD patients of different ages, which was most distinguished in patients younger than 65 years. Conclusion: COPD patients have a higher risk of developing dementia or cognitive impairment compared to those without COPD, and this risk is not affected by gender but seems to be associated with age.